Problem-Solving Ability in Four Models of Learning (Universitas Negeri Semarang, 2018)
The demands of the 21st century and curriculum 2013 is mastered various skills one problem-solving. 2013 curriculum gives a model learning using PBL, PjBL, and DL in exercising a high-level way of thinking that is problem-solving, moreover in the model can give influence on the learning outcomes of students. This research aims to: a) know the difference or not on the ability of problem-solving learning model in four, b) knowing the effectiveness of PBL learning model, the PjBL, DL, and DI against the ability of problem-solving. The research method used was a quasi-experimental design with a posttest-only control group design. The design of this study uses four groups of experiments. The research population was 224 students. Samples taken in cluster random sampling amounted to 128 students. Problem-solving ability data drawn from tests given to students in the form of multiple choice reasoned with the amount of 20 items. The results showed that a) there may be differences in the problem-solving ability of four models of learning are shown with PBL enough (59%), the PjBL of enough (55%), DL enough (51%), and DI enough (50%), b) effectiveness of four models of learning seen from the highest value on every dimension of problem-solving with the results: 1) the model PBL, PjBL, DL, including both categories and models DI categories include enough on solving dimension of meaning or the identification of problems, 2) PBL model including both categories, while the model PJBL, DL, and DI enough categories in dimension using concrete measures to address the problem or design and manage projects, 3) PBL model, PJBL, DL, and DI including sufficient dimensions category acquires, process, interpret, and analyze information to make a decision, 4), PBL, PjBL, DL, and DI including sufficient dimensions involved in the process of investigation solve, and 5), model PBL, PjBL, DL, and DI including sufficient dimensions make connections and transfer learning from one the situation to the other. Thus, the model of PBL, PjBL, and DL is good enough to measure problem-solving ability, but teachers are expected to minimize the use of the model DI this model is still centered on teachers so that students are less than optimal in developing problem-solving abilities.